Sovereign nations [videorecording (VHS)] (KSPS Home Video, 1998)
Looks at the culture and history of the native Americans of the inland northwest. Explores the arrival of the Europeans and missionaries, the various treaties that came into existence, the establishment of various reservations, the allotment period and the current exploration of treaty rights.